Application of fuzzy TOPSIS method for risk evaluation in development and implementation of solar park in India. Issue 14 (17th November 2022) - Ranganath, N.; Sarkar, Debasis; Patel, Preet; Patel, Smit
Abstract: Renewable energy sector projects like development and implementation of solar power plants are given preference and boost in India to meet the target for generation of green and clean energy. Like other complex infrastructure projects, the solar power projects also face risks and uncertainties throughout all the phases. Although new techniques and methods are introduced, risk assessment for projects remains an unstructured problem that depends on human expertise. This paper aims at identifying the risks involved and associated with all the phases of the solar power project in India and develop a methodology of risk analysis through application of Fuzzy TOPSIS (Technique for Order Preference by Similarities to Ideal Solution) methodology. Risk severity has been computed through computation of Fuzzy Positive Ideal Solution (FPIS), Fuzzy Negative Ideal Solution (FNIS) and Closeness Coefficient (CC). It has been observed that the risk severity of phase 1 ranges between moderate to high. Phase 2 ranges between high to very high, phase 3 and 4 are very high and finally phase 5 varies between moderate to high. Thereby the project authorities cannot afford to ignore any of the phases. Furthermore, suitable corrective and preventive risk mitigation measures have been recommended.